(untitled) (Research, Society and Development, 2021)
Objective: To characterize Health Extension Projects at a university in the northern region of Brazil, establishing relations between Public Policies and Health Education. Methods: Exploratory descriptive research with a qualitative approach with Bardin Content Analysis. The final reports of the Curricular Extension Actions (ACE) of the Physical Education, Nursing, Pharmacy, Physiotherapy, Medicine and Dentistry courses, performed in the years 2016 and 2017, were analyzed, using an instrument containing questions related to the characterization of the project, activities that included Public Policies and Health Education. Results: The speeches of the community served were listed in categories that best represented the impacts of extension actions related to Public Policies and Health Education. Extension was pointed out as a tool to transform habits in the community and improve student learning. Conclusion: The actions contemplated the implementation of public health policies through health education with reach in the community. However, it is necessary to promote health to populations in situations of vulnerability with a wider reach of social groups.